Activating Inert Sites in Cobalt Silicate Hydroxides for Oxygen Evolution through Atomically Doping. Issue 2 (22nd August 2021) - Zhu, Jiexin; Xia, Lixue; Yang, Wenxuan; Yu, Ruohan; Zhang, Wei; Luo, Wen; Dai, Yuhang; Wei, Wei; Zhou, Liang; Zhao, Yan; Mai, Liqiang
Abstract : Metal silicate hydroxides have been recognized as efficient oxygen evolution reaction (OER) electrocatalysts, yet tailoring of their intrinsic activity remains confused. Herein, Fe had been incorporated into cobalt silicate hydroxide nanosheets and the resulted material achieves a competitive OER catalytic activity. It is found that the doping state obviously affects the electrical transport property. Specifically, highly dispersed Fe atoms (low‐concentration Fe doping) trigger slight electron transfer to Co atoms while serried Fe (high‐concentration Fe doping) attract vast electrons. By introducing 6 at.% Fe doping, partial relatively inert Co sites are activated by atomically dispersed Fe, bearing an optimal metal 3 d electronic occupation and adsorption capacity to oxygen intermediate. The introduced Co−O−Fe unit trigger the π ‐donation effect and decrease the number of electrons in π *‐antibonding orbitals, which enhance the Fe−O covalency and the structural stability. As a result, the sample delivers a low overpotential of 293 mV to achieve a current density of 10 mA cm −2 . This work clarifies the superiority of atomically dispersed doping state, which is of fundamental interest to the design of doped catalyst. Abstract : Ultrathin cobalt silicate hydroxide nanosheets with atomically dispersed Fe doping have been applied as efficient oxygen evolution catalysts. The slight electron transfer between Fe and Co bring in optimal metal 3 d electronic occupation, enhanced oxygen adsorption capacity and structural stability, thus exhibiting favorable OER performance.